KEAKTIFAN BELAJAR SISWA SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Eliana Yunitha Seran; Mardawani Mardawani; Anna Marganingsih; Veni Lestari (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
The background of this study is to find out how effective isstudying online and offline during pandemic covid-19 at the primary school.Various obstacles duringpandemics also influence the effectiveness of students to study because there was a change from studying face to face as usual to studying online. The purpose of this study is to know how effectivethe students to studying onlineduring pandemic covid-19. The study is based on a quantitative research method. A data collection is a survey. The population in this study were 225 students and only69 valid samples of primary school students. The result of the study found that the effectiveness of the students who studied onlinehas a strong category with a score total is 6537, the average is 94,73 and the percentage of the score obtained 75,79 %.Based on the hypothesis test, the value of thitungis greater than the value ofttabel, which is 3,57 > 1,66, then Ho is rejected and Ha is accepted. From the results of the study, it was found that the effectiveness of the studentswho studied online during the pandemic was more than 70%.